Determinan Nilai Perusahaan dengan Mediasi Profitabilitas pada Perusahaan Properti dan Real Estate yang terdaftar di Bursa Efek Indonesia periode tahun 2020-2023 (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to analyze the effect of capital structure and liquidity on firm value with profitability as a mediating variable in the property and real estate sector on the Indonesia Stock Exchange (IDX) for the period 2020–2023. Capital structure is proxied by DAR and DER, liquidity by Current Ratio and Cash Ratio, profitability by ROE and ROA, and firm value by PBV and Tobin’s Q. Using a quantitative method with purposive sampling technique, secondary data in the form of annual financial statements were analyzed using Partial Least Squares (PLS) through the SmartPLS application. The results show that capital structure has a significant negative effect on profitability, while liquidity does not have a significant effect on profitability. Profitability is proven to have a significant positive effect on firm value. Directly, capital structure and liquidity do not have a significant effect on firm value. The results of the mediation test indicate that profitability is unable to mediate the effect of capital structure and liquidity on firm value. This study is expected to contribute to the development of financial theory as well as serve as a consideration for management and investors in making financial decisions in the property and real estate sector.